DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI OPERASI HITUNG BILANGAN BULAT NEGATIF - Nurjannah Nurjannah; Danial Danial; Fitriani Fitriani (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This study is qualitative research that aims to describe and analyze the students’ learning difficulties in mathematical operations of negative integers. The subjects of the study were two students of 286 SDN 286 Pasaka. Giving test (diagnostic tests) and interviewing were conducted to collect the data. The results of the study show that basically the learning difficulties experienced by the subject IS and subject RV is the same: the lack of understanding of the concept of negative integer operations. Due to the lack of understanding of the concept, the subject is difficult to abstract, generalize and remember the concept or principle of operating negative integer operations. To overcome the learning difficulties experienced by students, the teacher must ensure students have mastered the prerequisite material, design ways of delivering teaching materials with effective communication and pay attention to family circumstances and social conditions of students.Keywords: Characteristics of items, item difficulties, discrimination